Anaesthetics depress the sensitivity of cortical neurones to L-glutamate. - Richards, C D (1976)
1 The effects of general anaesthetics on the responses of neurones to iontophoretically applied L-glutamate have been examined in slices of the guinea-pig olfactory cortex in vitro. 2 Concentrations of pentobarbitone, ether, methoxyflurance, trichloroethylene and alphaxalone that are known to depress synaptic transmission in the prepiriform cortex also depressed the sensitivity of prepiriform neurones to L-glutamate. 3 Halothane, in concentrations that depress synaptic transmission (less than 1%) did not alter sensitivity of neurones to glutamate. Higher concentrations (greater than 1% produced a dose-related depression of the glutamate sensitivity of neurones. 4 All four volatile anaesthetics tested caused some cells to alter their glutamate-evoked firing pattern to one in which the spike discharges were more closely grouped. Pentobarbitone and alphaxalone had no such effect. 5 If the sensitivity of the neurones to the endogenous excitatory transmitter is affected by anaesthetics in the same way as the glutamate-sensitivity, these results suggest that halothane depresses synaptic transmission by decreasing the amount of transmitter released from the nerve terminals, whereas the other anaesthetics depress the sensitivity of the post-synaptic membrane to the released transmitter.